Frequency Domain Analysis of F-16 Aircraft in a Variety of Flight Conditions - Özcan, Abdurrahim Bilal; Caferov, Elbrus (International Sustainable Aviation Research Society, 2022)
Examining the flight quality of an aircraft to ensure the stability of the aircraft, increase maneuverability, and make the aircraft easier to control by the pilot necessitates an examination of the natural stability of the system. Within the scope of the paper, the frequency domain response of the F-16 aircraft dynamics is analyzed using Simulink models considering two different flight regimes because the frequency-domain methods have many distinct and important advantages over time-domain methods. Aerodynamic, propulsive, and atmospheric databases are used to create the nonlinear model. The trim analysis for cruise flights is carried out to obtain trim parameters. The aircraft is numerically linearized using the small perturbation theory. The linearized dynamics for each trim condition are used to create transfer functions for each input. The linear model is subsequently examined in the frequency domain to obtain information about the dynamic behavior of the aircraft, and flight quality analysis was examined by considering the lateral and longitudinal modes of the aircraft by international standards. It has been clearly understood the stability augmentation system design has critical importance for the modes with unstable or long steady-state duration.
Keywords: Frequency Domain Analysis; F-16 Aircraft; Longitudinal Motion; Lateral Motion; System Dynamics; Uzay Mühendisliği; Aerospace Engineering